2018
DOI: 10.1016/j.bmcl.2018.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic analogues of the montanine-type alkaloids with activity against apoptosis-resistant cancer cells

Abstract: In a search of small molecules active against apoptosis-resistant cancer cells, a skeletal rearrangement of alkaloid haemanthamine was utilized to generate a series of compounds possessing the alkaloid montanine ring system. The synthesized compounds were found to inhibit proliferation of cancer cells resistant to apoptosis at micromolar concentrations. Selected compounds were also active against patient-derived glioblastoma cells expressing stem-cell markers. This is the first report describing the preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 34 publications
(33 reference statements)
0
52
0
Order By: Relevance
“…Although previous studies, as well as our work, have demonstrated that AA of the montanine type can effectively suppress viability and proliferation of human cancer cells, the molecular mechanism of this cytotoxic activity has not yet been fully explored and is still waiting to be described. Montanine and manthine showed strong in vitro growth inhibitory effect on three apoptosis-resistant cancer cell lines (A549, SKMEL-29, and U373) and three apoptosis-sensitive cancer cell lines (MCF7, Hs683, and B16F10) with IC 50 values between 5 and 31 µM [12]. In another recent study, C-2α-/C-2β-methoxy isomers montanine and coccinine were found to significantly affect the proliferation of human breast, colon, lung, and melanoma cancer cell lines over 48 h of treatment.…”
Section: Cytotoxic Study Of Isolated Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although previous studies, as well as our work, have demonstrated that AA of the montanine type can effectively suppress viability and proliferation of human cancer cells, the molecular mechanism of this cytotoxic activity has not yet been fully explored and is still waiting to be described. Montanine and manthine showed strong in vitro growth inhibitory effect on three apoptosis-resistant cancer cell lines (A549, SKMEL-29, and U373) and three apoptosis-sensitive cancer cell lines (MCF7, Hs683, and B16F10) with IC 50 values between 5 and 31 µM [12]. In another recent study, C-2α-/C-2β-methoxy isomers montanine and coccinine were found to significantly affect the proliferation of human breast, colon, lung, and melanoma cancer cell lines over 48 h of treatment.…”
Section: Cytotoxic Study Of Isolated Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…Professor Einstein resulted in the isolation of 23 known AA , and a new alkaloid (24). The compounds were analyzed by various spectroscopic methods (GC-MS, LC-MS, and 1D and 2D NMR spectroscopy) and identified by comparison with literature data as masonine (1) [22], homolycorine (2) [23], ismine (3) [24], caranine (4) [25], galanthamine (5) [26], narwedine (6) [27], lycoraminone (7) [28], pluviine (8) [25], incartine (9) [29], galanthine (10) [30], lycoramine (11) [26], epinorgalanthamine (12) [31], norlycoramine (13) [32], haemanthamine (14) [32], hippeastrine (15) [33], epimaritidine (16) [34], lycorine (17) [35], tazettine (18) [36], eugenine (19) [37], norpluviine (20) [38], 9-O-demethylmaritidine (21) [39], pancracine (22) [40], and 9-O-demethylhomolycorine (23) [23] (Figure 1). The alkaloids that were isolated were representatives of the homolycorine (1,2,15,19,23), galanthamine (5,6,…”
Section: Isolation and Identification Of Amaryllidaceae Alkaloids Fromentioning
confidence: 99%
See 3 more Smart Citations